Integrated stratigraphy of Early Aptian black shales in the Boreal Realm: calcareous nannofossil and stable isotope evidence for global and regional processes - C. Bottini; J. Mutterlose (Newsletters on Stratigraphy, 2012)
The Early Aptian is marked by an event of widespread anoxia in the oceans, known as Oceanic Anoxic Event (OAE)1a. During this time the Lower Saxony Basin (LSB), constituting the southern extension of the Boreal-Arctic Sea, was affected by the deposition of finely laminated black shales of the Fischschiefer (FS) considered to be the product of OAE 1a. This study focuses on Upper Barremian-Lower Aptian sediments from three different localities in northern Germany encompassing the FS. The proposed integrated litho-, bio-, and chemo-stratigraphy provides an accurate time control for correlation and for detecting the timing of the processes that affected the LSB during the deposition of the FS. The paleoecological and paleoclimatic reconstructions based on calcareous nannofossils indicate that sedimentation during the Late Barremian was mostly depending on regional conditions related to the paleogeography of the LSB. The deposition of the FS was instead mainly driven by mechanisms operating on a global scale and associated to OAE 1a: a warming event, also detected at low latitudes, was accompanied by high primary productivity and influx of cosmopolitan taxa through new seaways opened to the Tethys. In the late Early Aptian local factors prevailed again on sedimentation although paralleled by a decrease in temperature documented at different latitudes which probably favoured the migration of Boreal species southwards.